2021
DOI: 10.3390/biology10050382
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Mitochondrial Translocator Protein (TSPO) Gene Decreases Oxidative Retinal Pigment Epithelial Cell Death via Modulation of TRPM2 Channel

Abstract: The current results indicated the possible protective actions of 18 kDa mitochondrial translocator protein (TSPO) deletion on TRPM2 stimulation, mitochondrial free ROS (Mito-fROS) and apoptotic harmful actions in the cells of adult retinal pigment epithelial19 (ARPE19). There was a direct relationship between TSPO and the disease of age-related macular degeneration. The nature of TSPO implicates upregulation of Mito-fROS and apoptosis via the activation of Ca2+ channels in ARPE19, although deletion of TSPO gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The generation of ADPR in the SH-SY5Y could be decreased by the inhibitors of PARP-1 (Butenko et al 2012 ; Akyuva and Nazıroğlu 2020 ). The DPQ and PJ34 are two well-known PARP1 inhibitors in the TRPM2 channel experiments (Armağan and Nazıroğlu 2021 ; Özkaya et al 2021 ). Hence, I wanted to test modulator actions of ADPR production through DPQ and PJ34 treatment on the cCa 2+ concentrations in the SH-SY5Y cells.…”
Section: Resultsmentioning
confidence: 99%
“…The generation of ADPR in the SH-SY5Y could be decreased by the inhibitors of PARP-1 (Butenko et al 2012 ; Akyuva and Nazıroğlu 2020 ). The DPQ and PJ34 are two well-known PARP1 inhibitors in the TRPM2 channel experiments (Armağan and Nazıroğlu 2021 ; Özkaya et al 2021 ). Hence, I wanted to test modulator actions of ADPR production through DPQ and PJ34 treatment on the cCa 2+ concentrations in the SH-SY5Y cells.…”
Section: Resultsmentioning
confidence: 99%
“…Although they lack some physiological characteristics of the RPE, ARPE-19 cells are regarded as a reliable model for investigating RPE cell metabolism [ 9 , 11 , 12 ]. The detrimental oxidative and apoptotic effects of medicines such as HCQ and chloroquine have been experimentally studied using ARPE19 cells as a model of the human RPE [ 9 , 11 , 12 ]. Recently, it was also reported that a TRPM2 channel naturally exists in ARPE19 cells [ 16 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the CASY cell viability analyses, the cell viability analyses were repeated in the cells by using the MTT test [ 11 , 12 ]. For the analyses, the ARPE19 cells were seeded in ninety-six-well plates at an initial density of 1 × 10 6 cells/well and were treated with 100 µl of 5 mg/ml of MTT in PBS was added to each well, and incubated for 4 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations